Study of dielectric relaxation and thermally activated a.c. conduction in multicomponent Ge10−xSe60Te30Inx (0 ≤ x ≤ 6) chalcogenide glasses using CBH model - Singh, Pravin Kumar; Sharma, S.K.; Tripathi, S.K.; Dwivedi, D.K. (Results in physics, 2019)
Amorphous Ge10−xSe60Te30Inx (0 ≤ x ≤ 6) chalcogenide glasses were prepared by melt quench technique. Surface morphology with the chemical composition of the prepared glass was examined using SEM and EDS analysis respectively. Dielectric properties and a.c. conductivity of the multicomponent Ge10−xSe60Te30Inx (0 ≤ x ≤ 6) chalcogenide glasses have been examined in the frequency range 100 Hz–1 MHz and temperature range 303–328 K. It was noticed that dielectric constant and dielectric loss decreases with the increase of frequency and increases with the increase of temperatures. Frequency and temperature dependence of dielectric constant was explained by orientational polarization. The variation of dielectric loss with frequency and temperature was explained by conduction loss and theory of single polaron hopping of charge carriers suggested by Elliot and Shimakawa for chalcogenide glasses. The experimental results show that a.c. conductivity follows the power law ωs where s < 1 and value of s decreases with the increase of temperature. The present findings of a.c. conductivity and variation of s with temperatures are reasonably well interpreted in terms of CBH model.